Green Synthesis of Nano Zn3(PO4)2 Using Curcuma Extract and Their Effect on SK-OV-3 Human Ovarian Cancer Cell Lines: Effects of Nano Zn3(PO4)2 at Human Ovarian Cancer Cell (Biological Sciences - PJSIR, 2025)
Zinc phosphate (ZnP) has many implementations in different areas. Nanoparticle materials synthesis utilizing plant extracts is an alternative to classic physical and chemical methods. The biological synthesis of nanoparticles is of significant importance due to its simplicity, eco-friendliness and extensive antimicrobial activity.